EXTRACTIUON AND LYOPHILIZATION OF THE LOW DENSITY OF LIPOPROTEIN INSTEAD OF EGG YOLK ON SOME SEMEN PARAMETERS OF AWASSI RAMS - & Al-Saab, Al-Subaihawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to explain the possibility of lyophilization of low– density lipoprotein (LDL) that is extracted from the egg yolk to be used instead of the egg yolk in an extender semen that belong to the Awassi sheep and their effect on the characteristics of the semen after five days of cryopreservation, as well as to get low-density Lipoprotein, steriled and lyophilized (powder) lipoprotein that can be stored for a long time to used when needed. The study was conducted in the from July 2015 to February 2016. The first stage started from July until August 2015 the (LDL) was extracted from fresh egg. The second stage in August 2015. the liquid (LDL) has been lyophilized and turn into powder that is packed in vials, steriled vials and then was stored in 0°C. The third stage was conducted from January to February 2016 in the college of Agriculture/ University of Baghdad. the semen was collected from four of the Awassi rams of the age (2– 4) years and the samples was collected by using artificial vagina. After that the sample was divided on the experimental treatments evenly 1ml/ transaction by using extender Tris. The dilution ratio was 1: 10. The effect of the different concentrations had been studied of the LDL on the characteristic of semen and three concentration of the LDL were used (3.2, 4.8 and 6.2%) for the transactions T1, T2,T3 respectively and the control treatment (20% EY).The effect of the lyophilized LDL was studied on some characteristic of sperm when cryopreserved under the temperature 5°c for five days. The Results of the experiment to varying differences between transactions in sperm characteristics as treatment outperformed T3 (P <0.05) in the individual movement in the 2nd and 3rd days and did not notice a significant difference on the other days, while a significant difference in the percentage of live sperm among the treatments and control were observed viability of keeping LDL of sperm higher was than it is in the control treatment of the plasma membrane as treatment outperformed T2 and T3 (P <0.05) on the treatment of control on the 3rd, 4th and 5th of conservation was also excel themselves transactions in susceptibility saved for acrosome on different days of conservation compared with the control treatment as it overtook treatment T2 in the first two days and did not notice a significant difference on the 3rd and 4th among the treatments and control excelled treatments T2 and T3 (P <0.05) in 5th day of conservation to the control, we conclude from the foregoing that it is possible freeze-drying LDL and save the freeze and use it in time of need can also be used in lyophilized LDL thinners semen because of its positive impact in keeping sperm has been observed that the best concentration of sperm in maintaining the properties is 6.4% LDL compared with egg yolk and other transactions.